2018
DOI: 10.1093/cercor/bhy280
|View full text |Cite|
|
Sign up to set email alerts
|

Sensitive Period for Cognitive Repurposing of Human Visual Cortex

Abstract: Studies of sensory loss are a model for understanding the functional flexibility of human cortex. In congenital blindness, subsets of visual cortex are recruited during higher-cognitive tasks, such as language and math tasks. Is such dramatic functional repurposing possible throughout the lifespan or restricted to sensitive periods in development? We compared visual cortex function in individuals who lost their vision as adults (after age 17) to congenitally blind and sighted blindfolded adults. Participants t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 87 publications
(123 reference statements)
6
21
0
Order By: Relevance
“…The current results add to prior evidence of different cognitive sensitivity in the visual cortices of congenitally and adult-onset blind individuals (eg: Bedny, Konkle, Pelphrey, Saxe, & Pascual-Leone, 2010;Bedny, Pascual-Leone, Dravida, & Saxe, 2012;Büchel, Price, Frackowiak, & Friston, 1998;Burton, Diamond, & McDermott, 2006;Burton et al, 2002;Cohen et al, 1999;Kanjlia, Pant, & Bedny, 2018).…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…The current results add to prior evidence of different cognitive sensitivity in the visual cortices of congenitally and adult-onset blind individuals (eg: Bedny, Konkle, Pelphrey, Saxe, & Pascual-Leone, 2010;Bedny, Pascual-Leone, Dravida, & Saxe, 2012;Büchel, Price, Frackowiak, & Friston, 1998;Burton, Diamond, & McDermott, 2006;Burton et al, 2002;Cohen et al, 1999;Kanjlia, Pant, & Bedny, 2018).…”
Section: Discussionsupporting
confidence: 80%
“…The presence of responses to language in the visual cortex in individuals who become blind as adults is consistent with the observation of increased resting-state connectivity between Broca's area and the "visual" cortex in this population (Sabbah et al, 2016). Analogously, a recent study found increased resting-state connectivity between parts of the "visual" cortex that are responsive to number, and fronto-parietal number networks, even in adult-onset blind individuals (Kanjlia et al, 2018). This latter study also showed that resting-state increases are significantly smaller in the adult-onset as opposed to the congenitally blind population.…”
Section: A Sensitive Period In the Neural Substrates Of Language In Bsupporting
confidence: 86%
See 1 more Smart Citation
“…There is abundant evidence for increased activation of visual cortex for language tasks in early onset blindness as compared to sighted people Bedny et al, 2011a;Burton, 2003;Burton et al, 2003;Burton et al, 2002b;Lane et al, 2015;Röder et al, 2002), suggesting a role for local reweighting and better utilization of inputs. Similarly, evidence for differences in the extent of recruitment depending on the timing of blindness onset also suggests that early-onset blindness involves more than unmasking, and that such additional processes are time-sensitive (Bedny et al, 2011b;Burton et al, 2003;Burton and McLaren, 2005;Burton et al, 2002a;Burton et al, 2002b;Cohen et al, 1999;Kanjlia et al, 2018). However, our results reveal a key piece of this puzzle by explaining how language information arrives in early visual cortex.…”
Section: Discussionsupporting
confidence: 53%
“…According to this view, one should assume that crossmodal plasticity would express similarly also when the onset of blindness occurs late in life. In contrast with this hypothesis, previous studies suggested that, despite late blind individuals showing enhanced occipital recruitment for non-visual stimuli, this recruitment might not be as functionally organized as in the case of early blindness (Marina Bedny, Pascual-Leone, Dravida, & Saxe, 2012;Collignon et al, 2013;Kanjlia, Pant, & Bedny, 2019). In addition, two studies including a small number of LB participants (n=4 in Jiang et al, 2016;n=5 LB in Stevens & Weaver, 2009) showed that the functional profile of the auditory cortex in LB might be more similar to the one of the sighted controls than to the congenitally blind group.…”
Section: Introductionmentioning
confidence: 76%